Mycophenolate mofetil (MMF) for the treatment of connective tissue disease‐associated interstitial lung disease (ILD) - Stolagiewicz, Natalie E (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy of mycophenolate mofetil in the treatment of connective tissue disease‐associated interstitial lung disease.